2016
DOI: 10.5812/jjm.29331
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Sepsis Therapy Using Sepia Officinalis

Abstract: Background:Sepsis remains a major problem for both scientists and clinicians. Cecal ligation and puncture (CLP) is considered the gold standard for animal models of sepsis. The undesirable side effects of certain antibiotics have forced scientists to discover new, natural, and safe antimicrobial agents, such as cephalopods, which are known to display significant antimicrobial activity.Objectives:The present investigation aims to evaluate the in vitro and in vivo antibacterial and antiseptic efficacy of Sepia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…(mold) Nithya et al determined using the sulphorhodamine B (SRB) method against hepatocellular carcinoma (HepG2) cell line. Soliman et al (2015) found that S. officinalis ink extract had anticancer effects against Ehrlich ascites carcinoma (EAC) in Swiss albino mice. He added that Sepia ink extract inhibits tumour growth in the ascites tumour model.…”
Section: Anti-cancer Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…(mold) Nithya et al determined using the sulphorhodamine B (SRB) method against hepatocellular carcinoma (HepG2) cell line. Soliman et al (2015) found that S. officinalis ink extract had anticancer effects against Ehrlich ascites carcinoma (EAC) in Swiss albino mice. He added that Sepia ink extract inhibits tumour growth in the ascites tumour model.…”
Section: Anti-cancer Activitymentioning
confidence: 99%
“…Fahmy and Soliman (2013) investigated the antioxidant activity of cuttlefish (S. officinalis) ink extract using 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging and lipid peroxidation assays and measured promising antioxidant properties from the Sepia ink extract. Another study by Soliman et al (2015) was conducted to compare the antioxidant and anti-cancer activities to 5-fluorouracil (5-Fu) in vivo, where Swiss albino mice were used as experimental animals, and they found good antioxidant properties.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Epidemiological data shows that sepsis affects more than 18 million people worldwide every year, with the incidence of sepsis increasing by 1.5−8.0% annually. 4,5 In the intensive care unit, sepsis has surpassed myocardial infarction as one of the leading causes of death. 6 As research on the mechanisms of sepsis deepens, drug development for sepsis has progressed.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis, characterized by a systemic infectious inflammatory response, is also a major factor in morbidity and mortality of surgical patients . The hyperinflammatory response of sepsis can lead to the release of multiple inflammatory mediators in the body, ultimately causing multiple organ dysfunction, coagulation, and even death. , Epidemiological data shows that sepsis affects more than 18 million people worldwide every year, with the incidence of sepsis increasing by 1.5–8.0% annually. , In the intensive care unit, sepsis has surpassed myocardial infarction as one of the leading causes of death …”
Section: Introductionmentioning
confidence: 99%